Factors Associated with Health-Related Quality of Life in Older Adults Beneficiaries of Social Programs Living in Rural Areas of Huancavelica, Peru - Valenzuela-Oré, Félix (2025)
Objective: To evaluate associated factors with health-related quality of life in older adults’ beneficiaries of the “Pensión 65” program in Angaraes, Huancavelica. Materials and methods: A cross-sectional study. 160 people over 65 years-old were surveyed using the SF-36 questionnaire to measure health-related quality of life through eight dimensions (physical function, physical role, corporal pain, emotional role, general health, vitality, social function and mental health) and two components (physical health-SF and mental health-SM). Additionally, data about demographic and social characteristics was collected. The relationship with health-related quality of life was evaluated through multivariable models (multiple linear regression). Results: A statistically significant relationship was found between the SM component scores and primary or secondary educational level (β: -3.080 [95CI% -5.558; -0.602]), having a partner (β: 2.456 [95CI% 0.347;4.565]), being unemployed (β: -4.412 [95CI% -8.172; -0.652]), and the place where the sons live: they live in the same house (β: -4.518 [95CI% -7.634;-1.403]) , live in the same community/neighborhood (β:-4.301 [95CI% -7.027;-1.575]). Conclusion: The educational level of at least primary school, having a partner, being unemployed and the place where the sons live are factors associated with the quality of life related to health (mental health component) in older adults’ beneficiaries of the “pension 65” program, residents in two districts of the province of Angaraes - Huancavelica.